Just my soul responding rhythm and blues, black consciousness, and race relations - Ward, Brian (Univ. of California Press, 1998)
"Instead of seeing black music as a mere reflection of mass struggle, Ward argues that [rhythm and blues]...formed a crucial public arena for battles over civil rights, racial identity, indidivual pride, and economic empowerment."--Back cover.